Continuous design decision support - Kleebaum, Anja; Paech, Barbara (Managed software evolution, 2019)
The main challenges of rational decision-making, documentation, and exploitation are intrusiveness of the activities and consistency between decisions and between decisions and artefacts. This chapter presents three approaches that address these challenges and that contribute to a continuous design decision support: They assist the design decision-making by using a catalogue of design patterns. Once the design decisions are documented, they are made visible in the program code and are accessible from other artefacts such as requirements to increase the developers’ awareness of the decisions and to enable an easy exploitation. In addition, short-cycled practices in continuous software engineering are used to support the documentation and exploitation of design decisions.